2018
DOI: 10.1021/acsaem.8b00885
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing of a Complete Lithium Ion Battery with Fused Filament Fabrication

Abstract: The ability to 3D print lithium ion batteries (LIBs) in an arbitrary geometry would not only allow the battery form factor to be customized to fit a given product design but also facilitate the use of the battery as a structural component. A major hurdle to achieving this goal is the low ionic conductivity of the polymers used for 3D printing. This article reports the development of anode, cathode, and separator materials that enable 3D printing of complete lithium ion batteries with low cost and widely availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
164
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(183 citation statements)
references
References 91 publications
(183 reference statements)
3
164
1
Order By: Relevance
“…Mostly carbon allotropes, for instance, carbon nanotubes, carbon black and graphene, are used for the functionalization of the material composites. Besides effects on electrical conductivity, certain studies underline the positive effect of fillers on mechanical properties, especially Young's modulus and tensile strength [2,[18][19][20][21][22]. Due to the direction of the deposited material, some fillers (e.g., graphene flakes) are oriented in the extrusion direction and, thus, the anisotropy of conductivity and tensile strength or Young's modulus increases [20].…”
Section: Characterization Of Electrically Conductive Composite Materimentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly carbon allotropes, for instance, carbon nanotubes, carbon black and graphene, are used for the functionalization of the material composites. Besides effects on electrical conductivity, certain studies underline the positive effect of fillers on mechanical properties, especially Young's modulus and tensile strength [2,[18][19][20][21][22]. Due to the direction of the deposited material, some fillers (e.g., graphene flakes) are oriented in the extrusion direction and, thus, the anisotropy of conductivity and tensile strength or Young's modulus increases [20].…”
Section: Characterization Of Electrically Conductive Composite Materimentioning
confidence: 99%
“…Hampel et al (2017) [4] showed the integration of electrical components by means of a 3d printed flashing circuit, for instance, a push button, resistors, and cavities for the integration of a capacitor or an LED. Furthermore, to demonstrate the potential of functional integration of additively manufactured electrical components, Reyes et al (2018) [19] realized a lithium ion battery that is integrated into side…”
mentioning
confidence: 99%
“…h) 3D‐printed bangle battery lighting up an LED. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Major Printing Methods For 3d‐printed Batteriesmentioning
confidence: 99%
“…The direct 3D printing approach for batteries is able to facilitate the creation of such kinds of systems. For example, Reyes et al developed a fully printed and customized Li‐ion battery with an FDM 3D printer to accommodate a given product design . By screening nine combinations of carbonate solvents and three electrolytes for commercial lithium‐ion batteries, they successfully improved the ionic conductivity of PLA to 0.085 mS cm −1 , about four times higher than the previously reported values .…”
Section: Major Printing Methods For 3d‐printed Batteriesmentioning
confidence: 99%
“…Common additives used in polymer matrix for EESDs are various conductive materials like ABS/graphene [26], ABS/carbon [27], PLA/graphene [28] and even PLA/LTO/carbon and PLA/LFP/carbon [29]* which are essential for electrode fabrication in lithium ion batteries. A good example is a recent study [30]** where three conductive agents (Super-P, MWCNTs, graphene) and two active materials (Lithium titanate, lithium manganese oxide) were blended with PLA to test the printability, conductivity and charge storage capacity of the new composite.…”
Section: Materials and Methods Considerationmentioning
confidence: 99%